A knowledge–based system for strip–layout design for progressive deep drawing dies. (2nd October 2013) - Naranje, Vishal; Kumar, Shailendra
Strip–layout design is one of the most critical steps in the design of progressive deep drawing die. It is a skilled and experienced–based activity. This paper presents a Knowledge–Based System (KBS) for automation of strip–layout design of sheet metal parts produced on progressive deep drawing dies. The proposed system is developed using production rule–based KBS approach of artificial intelligence (AI). It comprises eight modules to impart recommendations to the user for selection of proper size of stock strip, identification and sequencing of operations, selection of proper piloting scheme, and number of stations and staging of operations on progressive deep drawing die. Finally, the system models the blank layout and strip–layout automatically in the drawing editor of AutoCAD. The proposed system is flexible, user–interactive and its low cost of implementation makes it affordable for small and medium scale sheet metal industries.